Community structure and ecological quality assessment of macrobenthos in the coastal sea areas of Northern Yantai, China - Li, Fan; Ma, Yuanqing; Song, Xiukai; Li, Shaowen; Zhang, Xiaomin; Wang, Xiuxia; Wang, Tiantian; Sun, Zhenning (Frontiers in Marine Science, 2022)
Four cruises in the Bohai Sea and northern Yellow Sea off Yantai, China, in April and August of 2020, collected data on the species composition and community structure characteristics of macrobenthos in these sea areas. Temporal and spatial changes in the dominant macrobenthic species between April and August were also analyzed. The M-AMBI and environmental data were used to assess the benthic ecological quality of the coastal waters off Yantai. The results revealed differences in macrobenthic community structure and ecological quality status between the two sea areas. The main findings are as follows: A total of 7 phyla and 153 macrobenthic species were collected; 113 and 101 species were recorded in the Bohai Sea and northern Yellow Sea areas, respectively, and estimated abundance was 301 ind. m-2 and 598 ind. m-2 (p < 0.01), and biomass was 10.20 g m-2 and 14.65 g m-2, respectively. The dominant species comprised small-sized polychaetes and bivalves. The main dominant species were Glycinde bonhourei, Micronephthys oligobranchia, Sternaspis chinensis, and Moerella hilaris. The number of species differed significantly between seasons (p < 0.05). A comparison of the dominant species and community structure of the macrobenthos between seasons showed that more obvious replacement occurred in the Bohai Sea. There were major differences in community structure of the macrobenthos between the two areas. Macrobenthos abundance was positively correlated with depth, dissolved oxygen, and sand substrate, and negatively correlated with bottom-water temperature, pH, and fine silt or clay substrate. In April, sites with low ecological value were at the ports of Laizhou and Longkou and Yangma Island, with the water quality likely affected by intensive bivalve aquaculture, port activities, and river discharge; in August, low-ecological-value sites were the middle of Laizhou Bay, Longkou Port, west of Daheishan Island, and coastal water between the cities of Yantai and Weihai. Overall, the sea areas off Yantai were generally deemed to be in a “good” state of ecological quality.